EFFECT OF HUMANISTIC PRINCIPLES BASED ACTIVE-COLLABORATIVE SUPERVISION ON TEACHERS’ COMPETENCE - Wiyono, Bambang Budi; Kusmintardjo, Ali Imron (Acta Scientiae et Intellectus, 2024)
One of the most prioritized programs in Indonesian education is the improvement of education quality. To do so, it is required to improve teachers’ competence in doing their works. The purpose of this research is to investigate the effectiveness of humanistic based active-collaborative supervision in order to improve teachers’ competence. The research design used in this research is pretest posttest experimental design. The sample was 38 teachers which were chosen by using quota random sampling method, while the data was collected by using test, observation, and documentation. The result of data collection was analyzed by using descriptive statistic and t-test. The result showed that humanistic based active-collaborative supervision was very effective in order to improve teachers’ professional competence in carrying out their duties.